Immunomodulation of phloretin by impairing dendritic cell activation and function - Lin, Chi-Chen; Chu, Ching-Liang; Ng, Chin-Sheng; Lin, Ching-Yen; Chen, Der-Yuan; Pan, I.-Hong; Huang, Kao-Jean (Food & function, 2014)
Dietary compounds in fruits and vegetables have been shown to exert many biological activities. In addition to antioxidant effects, a number of flavonoids are able to modulate inflammatory responses. Here, we demonstrated that phloretin (PT), a natural dihydrochalcone found in many fruits, suppressed the activation and function of mouse dendritic cells (DCs). Phloretin disturbed the multiple intracellular signaling pathways in DCs induced by the Toll-like receptor 4 (TLR4) agonist lipopolysaccharide (LPS), including ROS, MAPKs (ERK, JNK, p38 MAPK), and NF-κB, and thereby reducing the production of inflammatory cytokines and chemokines. Phloretin also effectively suppressed the activation of DCs treated with different dosages of LPS or various TLR agonists. The LPS-induced DC maturation was attenuated by phloretin because the expression levels of the MHC class II and the co-stimulatory molecules were down-regulated, which then inhibited the LPS-stimulating DCs and the subsequent naïve T cell activation in a mixed lymphocyte reaction. Moreover, in vivo administration of phloretin suppressed the phenotypic maturation of the LPS-challenged splenic DCs and decreased the IFN-γ production from the activated CD4 T cells. Thus, we suggest that phloretin may potentially be an immunomodulator by impairing the activation and function of DCs and phloretin-contained fruits may be helpful in the improvement of inflammation and autoimmune diseases. Dietary compounds in fruits and vegetables have been shown to exert many biological activities. In addition to antioxidant effects, a number of flavonoids are able to modulate inflammatory responses.